Expression of P450arom and Estrogen Receptor Alpha in the Oviduct of Chinese Brown Frog (Rana dybowskii) during Prehibernation - Ji Weng; Yuning Liu; Ying Xu; Ruiqi Hu; Haolin Zhang; Xia Sheng; Gen Watanabe; Kazuyoshi Taya; Qiang Weng; Meiyu Xu (International Journal of Endocrinology)
One specific physiological phenomenon of Chinese brown frog (Rana dybowskii) is that its oviduct expands prior to hibernation instead of expanding during the breeding period. In this study, we investigated the expression of P450arom and estrogen receptors α and β (ERα and ERβ) in the oviduct of Rana dybowskii during the breeding period and prehibernation. The results of the present study showed that there were significant differences in both oviductal weight and size with values markedly higher in prehibernation than in the breeding period. P450arom was observed in stromal tissue in both the breeding period and prehibernation. ERα was expressed in stromal tissue and epithelial cells in both periods, whereas ERβ could not be detected. The mean protein and mRNA levels of P450arom and ERα were significantly higher in prehibernation as compared to the breeding period. Besides, oviductal content of 17β-estradiol was also higher in prehibernation than in the breeding period. These results suggested that estrogen may play autocrine/paracrine roles mediated by ERα in regulating the oviductal hypertrophy during prehibernation.